Emulsion and article
By introducing an ethylene carbonate structure (meth)acrylate polymer into the resin composition, heating and decomposition of carbon dioxide is used to reduce adhesion, the problem of difficult disassembly of adhesives in the prior art is solved, and the application of an environmentally friendly, easy-to-disassemble resin composition is realized.
Patent Information
- Application Number
- JP2023123093
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art uses water-soluble adhesives or thermally expanded microspheres, and it is difficult to effectively deal with the removal of large products or deep adhesives, and there is a lack of easy disassembly methods suitable for non-adhesive products, while increasing demand for environmentally friendly carbonate resin compositions.
Using (meth)acrylate polymers containing ethylene carbonate structures, the carbonate structure is used to interpret carbon dioxide release during heating, reducing adhesion to achieve easy disassembly, and using nuclear philic ion catalytic decomposition of carbonate structures.
An environmentally friendly resin composition using carbon dioxide as raw material is realized, and the carbon dioxide is distributed through heating is simplified to produce product disassembly, which is suitable for a variety of application scenarios.
Smart Images

Figure 2025019468000001 
Figure 2025019468000002 
Figure 2025019468000003
Abstract
Description
[Technical field]
[0001] The present invention relates to emulsions and articles made with the emulsions. [Background technology]
[0002] In recent years, from the perspective of environmental consideration, there has been a demand for electronic devices, electrical appliances, etc. that can be easily dismantled when they are no longer needed (easy dismantling). The parts that are generated through dismantling can be recycled or reused.
[0003] For example, when components constituting a product are attached to each other with an adhesive sheet, the adhesiveness of the adhesive sheet is reduced by an external stimulus to facilitate separation and peeling of the components. As an example of such an adhesive sheet, Patent Document 1 discloses an adhesive sheet made of a water-soluble adhesive that can be disassembled and peeled by immersing in water. Patent Document 2 discloses a heat-foamable removable adhesive tape that maintains high normal adhesive strength when bonded, but reduces adhesive strength by heating when separating and dismantling the bonded parts, allowing easy separation and dismantling. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2023-35332 A [Patent Document 2] JP 2014-214208 A Summary of the Invention [Problem to be solved by the invention]
[0005] When dismantling a product using the adhesive sheet disclosed in Patent Document 1, at least the adhesive sheet portion needs to be brought into contact with water; however, if the product is large or if the adhesive sheet is located deep inside the product and it is difficult for water to reach it, handling becomes difficult.
[0006] Furthermore, easy dismantling is sometimes required even for products that do not use adhesive sheets, and in such cases, the adhesive sheet disclosed in Patent Document 1 cannot adequately meet the requirements.
[0007] The average particle size of the thermal blowing agent (particularly the thermally expandable microspheres) disclosed in Patent Document 2 is generally about 1 to 80 μm from the standpoint of dispersibility, thin layer formability, etc., which cannot be adequately used depending on the application of the pressure-sensitive adhesive sheet.
[0008] Furthermore, in recent years, the demand for emulsion-type resin compositions has been increasing due to legal regulations, environmental considerations, and the like.
[0009] In recent years, with the growing demand for the creation of a recycling-based society, gases such as carbon dioxide, methane, and carbon monoxide have been attracting attention as sustainable carbon raw materials. For example, it has been reported that aliphatic polycarbonates that have only aliphatic (non-aromatic) groups in the main chain can be produced by copolymerizing carbon dioxide with epoxide, and there has been interest in chemical products and their production technologies that use gases such as carbon dioxide as raw materials. Carbon dioxide is considered to be a cause of global warming, so the effective use of carbon dioxide emitted from factories in the process of making various materials is useful for environmental protection.
[0010] Therefore, there is a demand for further options for emulsion-type resin compositions that use carbon dioxide as a manufacturing raw material and enable easier handling and dismantling.
[0011] The present invention has been made in consideration of the above circumstances, and has an object to provide a novel emulsion using carbon dioxide as a production raw material, and an article having a resin film formed from the emulsion composition. [Means for solving the problem]
[0012] In order to achieve the above object, first, the present invention provides a polymer comprising a monomer unit represented by the following formula (1): [ka] The present invention provides an emulsion characterized by containing, as a dispersoid, a (meth)acrylic acid ester polymer containing an ethylene carbonate-containing acrylic monomer having an ethylene carbonate structure represented by the following formula (Invention 1).
[0013] In the emulsion according to the above invention (Invention 1), the ethylene carbonate structure present in the (meth)acrylic acid ester polymer can be produced using carbon dioxide as a production raw material, and therefore carbon dioxide can be effectively utilized. In addition, the ethylene carbonate structure is decomposed by heat treatment together with a catalyst, and carbon dioxide is released. Therefore, even if a resin film (adhesive layer, etc.) formed using the above emulsion as a material is in close contact with another object, the carbon dioxide accumulates at the interface between the resin film and the object, thereby reducing the adhesion. As a result, it can be used in applications where the resin film can be easily separated from the object.
[0014] In the above invention (Invention 1), the (meth)acrylic acid ester polymer preferably contains the ethylene carbonate-containing monomer in an amount of 1% by mass or more and 99.9% by mass or less as a monomer unit constituting the polymer (Invention 2).
[0015] In the above inventions (Inventions 1 and 2), the ethylene carbonate-containing acrylic monomer is preferably a compound represented by any one of the following formulas (2) to (4) (Invention 3). [ka] (In the formula, n represents an integer of 0 or more.) [ka] (In the formula, n represents an integer of 0 or more.) [ka] (In the formula, n and m represent integers of 0 or more. X represents hydrogen or a methyl group.)
[0016] In the above inventions (Inventions 1 to 3), the particle size (D50) of the dispersoid is preferably 10 nm or more and 1 μm or less (Invention 4).
[0017] In the above inventions (Inventions 1 to 4), the (meth)acrylic acid ester polymer preferably contains acrylic acid as a monomer unit constituting the polymer (Invention 5).
[0018] In the above inventions (Inventions 1 to 5), the (meth)acrylic acid ester polymer is preferably obtained by emulsion polymerization of monomer units containing the ethylene carbonate-containing acrylic monomer (Invention 6).
[0019] In the above inventions (Inventions 1 to 6), it is preferable that the dispersion medium contains water (Invention 7).
[0020] Secondly, the present invention provides an article (Invention 8) having a resin film formed from a resin composition containing the above emulsion (Inventions 1 to 7).
[0021] In the above invention (Invention 8), it is preferable that the resin film is an adhesive layer and the article is an adhesive sheet (Invention 9). Effect of the Invention
[0022] The emulsion of the present invention has a small environmental impact because it uses carbon dioxide as a raw material for production. Furthermore, the emulsion of the present invention provides a new means for realizing easy dismantling because it is decomposed by heat treatment together with a catalyst and carbon dioxide is released. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, an embodiment of the present invention will be described. [Emulsion] The emulsion according to the present embodiment contains, as a monomer unit constituting a polymer, a monomer represented by the following formula (1): [ka] The (meth)acrylic acid ester polymer contains, as a dispersoid, an ethylene carbonate-containing acrylic monomer having an ethylene carbonate structure represented by the formula:
[0024] The ethylene carbonate structure can release carbon dioxide by decomposition. In particular, when an anion having nucleophilicity is present together with the ethylene carbonate structure, the anion performs a nucleophilic attack on a carbon atom constituting a carbonyl group in the ethylene carbonate structure, thereby efficiently decomposing the ethylene carbonate structure and releasing carbon dioxide.
[0025] By using the emulsion according to the present embodiment having such properties, it is possible to manufacture a product with excellent ease of dismantling. That is, the carbon dioxide released from the emulsion can be used to reduce the adhesion between members constituting the product, and as a result, the product can be easily dismantled. For example, when members are bonded together by a pressure-sensitive adhesive sheet manufactured using the emulsion as one of its materials, carbon dioxide is generated by the decomposition of the ethylene carbonate structure described above, and the carbon dioxide is accumulated at the interface between the pressure-sensitive adhesive sheet and the member, making it possible to physically separate the pressure-sensitive adhesive sheet and the member.
[0026] In addition, the above-mentioned nucleophilic anion is preferably generated from a nucleophilic anion generator capable of generating nucleophilic anions by a specific stimulus. In particular, when a nucleophilic anion generator that generates the above-mentioned anion by heating is used, the product in which the emulsion according to the present embodiment is used can be disassembled by heating as an external stimulus.
[0027] 1. (Meth)acrylic acid ester polymer The (meth)acrylic acid ester copolymer in this embodiment is not particularly limited as long as it contains, as a monomer unit constituting the polymer, an ethylene carbonate-containing acrylic monomer having an ethylene carbonate structure represented by the above formula (1).
[0028] The ethylene carbonate-containing acrylic monomer is not particularly limited as long as it contains an ethylene carbonate structure and has a (meth)acryloyl group (structure). A preferred example of the ethylene carbonate-containing acrylic monomer is a (meth)acrylic acid ester having a structure in which an organic group having an ethylene carbonate structure is bonded to a (meth)acryloyloxy group. An example of such a (meth)acrylic acid ester is represented by the following formula (2): [ka] acrylic acid ester represented by the following formula (3) [ka] or a methacrylic acid ester represented by the following formula (4): [ka] In any of the formulas (2) to (4), n and m are integers of 0 or more, and X is hydrogen or a methyl group.
[0029] Among the (meth)acrylic acid esters represented by the above formulas (2) to (4), from the viewpoint of easily releasing carbon dioxide gas, (meth)acrylic acid esters in which n and m are each 1 or more are preferred, and (meth)acrylic acid esters in which n and m are each 2 or more are preferred. The upper limit of each of the above n and m is not particularly limited, but from the viewpoint of polymerizability, it is preferably 10 or less, more preferably 6 or less, particularly preferably 4 or less, and even more preferably 3 or less. Among these, (meth)acrylic acid esters in which n=1 are preferred, and in particular, (2-oxo-1,3-dioxolan-4-yl)methyl methacrylate in which n=1 in formula (3) is preferred. The ethylene carbonate-containing monomer may be used alone or in combination of two or more.
[0030] As disclosed in JP 2006-335971 A, the ethylene carbonate-containing monomer can be produced by adding CO2 to the epoxy group of a (meth)acrylate having an epoxy group to introduce a carbonate group. That is, the (meth)acrylic acid ester copolymer according to the present embodiment using the ethylene carbonate-containing monomer can be produced using carbon dioxide as a production raw material, and therefore carbon dioxide can be effectively utilized.
[0031] The (meth)acrylic acid ester copolymer in this embodiment preferably contains 1% by mass or more of the ethylene carbonate-containing acrylic monomer, more preferably 5% by mass or more, and even more preferably 10% by mass or more. The (meth)acrylic acid ester copolymer in this embodiment preferably contains 99.9% by mass or less of the ethylene carbonate-containing acrylic monomer, particularly preferably 99.5% by mass or less, and even more preferably 99.0% by mass or less. By having a content of 99.9% by mass or less, the (meth)acrylic acid ester copolymer contains other constituent monomers sufficiently, and the (meth)acrylic acid ester copolymer is likely to have the desired performance. When the emulsion in this embodiment is used as a base material to form a pressure-sensitive adhesive layer, the content of the ethylene carbonate-containing acrylic monomer is, for example, preferably 1% by mass or more and 30% by mass or less, from the viewpoint of obtaining properties that can be used as a pressure-sensitive adhesive layer. From the viewpoint of effectively using carbon dioxide as a production raw material, the content of the (meth)acrylic acid ester copolymer in this embodiment is preferably 90% by mass or more and 99.9% by mass or less.
[0032] The (meth)acrylic acid ester copolymer in this embodiment may contain a monomer other than the above-mentioned ethylene carbonate-containing acrylic monomer as a monomer unit constituting the polymer. For example, examples of the monomer include (meth)acrylic acid alkyl esters having an alkyl group with 1 to 12 carbon atoms; monomers containing reactive functional groups such as hydroxyl groups, carboxyl groups, and amino groups; (meth)acrylic acid esters containing alkoxyalkyl groups; (meth)acrylic acid esters having aromatic rings such as phenyl (meth)acrylate; non-crosslinkable acrylamides such as acrylamide and methacrylamide; (meth)acrylic acid esters having non-crosslinkable tertiary amino groups such as N,N-dimethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate; vinyl acetate; and styrene. These may be used alone or in combination of two or more.
[0033] Among the above, the (meth)acrylic acid ester copolymer in the present embodiment preferably contains acrylic acid, which corresponds to a monomer containing a carboxy group, as a monomer unit constituting the polymer. By containing acrylic acid in the (meth)acrylic acid ester copolymer, it becomes easy to adjust the particle size of the (meth)acrylic acid ester copolymer as a dispersoid.
[0034] When the (meth)acrylic acid ester copolymer in this embodiment contains a monomer other than the above-mentioned ethylene carbonate-containing acrylic monomer as a monomer unit constituting the polymer, the content is preferably 0.1 mass% or more, particularly preferably 0.3 mass% or more, and more preferably 0.5 mass% or more. The content is preferably 99 mass% or less, particularly preferably 98 mass% or less, and more preferably 97 mass% or less. This makes it easy to adjust the particle size of the (meth)acrylic acid ester copolymer as a dispersoid while ensuring a sufficient amount of the above-mentioned ethylene carbonate structure in the (meth)acrylic acid ester copolymer.
[0035] In the emulsion according to the present embodiment, the particle size (D50) of the dispersoid composed of the (meth)acrylic acid ester copolymer is preferably 10 nm or more, more preferably 30 nm or more, particularly preferably 50 nm or more, and even more preferably 100 nm or more. The particle size (D50) is preferably 1 μm or less, particularly preferably 0.8 μm or less, and even more preferably 0.6 μm or less. When the particle size (D50) of the dispersoid is within the above range, it becomes easy to form a resin film that can release carbon dioxide well while having other desired properties. The details of the method for measuring the particle size (D50) are as described in the examples below.
[0036] When the emulsion according to this embodiment contains 90% by mass or more of the (meth)acrylic acid ester copolymer and has a particle size (D50) of 100 nm or more, it exhibits a structural color of any color due to Bragg reflection corresponding to the particle size, and various colors can be produced by controlling the particle size. Therefore, a resin film formed from a resin composition containing the emulsion according to this embodiment also has structural coloring properties and is suitable as a material for an article exhibiting a structural color, and is suitable for improving the design of the article.
[0037] 2. Method for producing emulsion Although the method for producing the emulsion according to the present embodiment is not particularly limited, it is preferable to emulsion-polymerize monomer units containing the above-mentioned ethylene carbonate-containing acrylic monomer to obtain an emulsion containing a (meth)acrylic acid ester copolymer as a dispersoid.
[0038] The emulsion polymerization may be carried out by a known method. For example, the emulsion polymerization may be carried out by stirring the ethylene carbonate-containing acrylic monomer, the other monomers as described above if desired, and an emulsifier in water as a dispersion medium, adding a polymerization initiator thereto, and stirring the mixture at a predetermined temperature.
[0039] The emulsifier is not particularly limited, but from the viewpoint of improving dispersion stability, anionic emulsifiers or nonionic emulsifiers are preferred, and anionic emulsifiers are more preferred.
[0040] Examples of anionic emulsifiers include sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkyl phenyl ether sulfate, polyoxyethylene polycyclic phenyl ether sulfate, sodium polyoxyethylene alkyl ether sulfate, and allyl alkyl sulfosuccinate. Examples of nonionic emulsifiers include polyoxyethylene alkyl ether and polyoxyethylene alkyl phenyl ether. Among these, polyoxyethylene polycyclic phenyl ether sulfate is particularly preferred. These emulsifiers may be used alone or in combination of two or more.
[0041] From the viewpoint of the stability of the emulsion polymerization reaction and the viewpoint of preventing the deterioration of physical properties due to the remaining unreacted emulsifier, the content of the emulsifier is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, relative to 100 mass of the total amount of all monomers. The content of the emulsifier is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and even more preferably 20 parts by mass or less, relative to 100 mass of the total amount of all monomers.
[0042] The polymerization initiator may be either water-soluble or oil-soluble, and examples thereof include azo compounds such as 2,2'-azobis(2-methylpropionamidine) dihydrochloride and 2,2'-azobis(2-amidinopropane) dihydrochloride, persulfates such as potassium persulfate, sodium persulfate, and ammonium persulfate, and peroxides such as benzoyl peroxide, t-butyl hydroperoxide, and hydrogen peroxide. Redox initiators such as a combination of a persulfate and sodium hydrogen sulfite, or a combination of a peracid and sodium ascorbate may also be used. The polymerization initiator may be used alone or in combination of two or more. Among these, ammonium persulfate is preferred from the viewpoint of excellent polymerization stability. These polymerization initiators may be used alone or in combination of two or more.
[0043] From the viewpoint of accelerating the polymerization rate, the content of the polymerization initiator is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the total amount of all monomers. The content of the polymerization initiator is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of the total amount of all monomers.
[0044] The temperature and stirring conditions after addition of the polymerization initiator or monomer may be any conditions that allow sufficient dispersion of the dispersoid, and for example, the temperature is preferably 60 to 90° C., particularly preferably 65 to 85° C., and more preferably 70 to 80° C. The stirring conditions are preferably 50 to 200 rpm, particularly preferably 70 to 180 rpm, and more preferably 100 to 150 rpm. The stirring time is preferably 10 to 180 minutes, particularly preferably 10 to 60 minutes, and more preferably 10 to 30 minutes.
[0045] Furthermore, it is preferable to further add an aqueous alkali solution such as aqueous ammonia, various water-soluble amines, an aqueous sodium hydroxide solution, or an aqueous potassium hydroxide solution to the emulsion obtained by emulsion polymerization to adjust the pH to 5 to 9, and particularly to 6 to 8.5. This makes it possible to improve the stability of the dispersion.
[0046] The solid content concentration of the obtained emulsion is preferably from 10 to 80% by mass, more preferably from 25 to 70% by mass, and further preferably from 45 to 65% by mass.
[0047] 3. How to use the emulsion The emulsion according to this embodiment can be used, for example, to produce a resin film, the details of which will be described later.
[0048] [Goods] Another embodiment of the present invention relates to an article comprising a resin film formed from a resin composition containing the above-mentioned emulsion.
[0049] The resin film is not particularly limited as long as it is formed from a resin composition containing the emulsion according to the present embodiment. More specific examples of the resin film include a pressure-sensitive adhesive layer, a self-supporting film, and a surface coat layer and an anchor coat layer formed on the surface of a specific substrate. In this specification, the term "self-supporting film" refers to a film that has a strength that can be handled by itself without being damaged even without a support, and can maintain the film shape.
[0050] The above-mentioned article depends on the type of resin film, for example, when the resin film is a pressure-sensitive adhesive layer, it is a pressure-sensitive adhesive sheet. When the resin film is a surface coating layer, the article can be a hard coat film having a substrate film and a surface coating layer provided on the substrate. When the resin film is a self-supporting film, the article can be a pressure-sensitive adhesive sheet or hard coat film having the self-supporting film, or a substrate film consisting of only the self-supporting film.
[0051] In the above-mentioned resin composition, the components other than the emulsion according to the present embodiment can be appropriately selected according to the type of resin film to be formed.For example, when forming a pressure-sensitive adhesive layer as the resin film, the resin composition preferably contains a pressure-sensitive adhesive component as the main material, and examples thereof include acrylic pressure-sensitive adhesives (acrylic polymers) and the like.In addition, when forming a surface coat layer as the resin film, the resin composition preferably contains a curable component as the main material.
[0052] In order to efficiently release carbon dioxide, the resin composition preferably contains a catalyst that promotes the decomposition of the ethylene carbonate structure. Examples of the catalyst include the nucleophilic anion generator.
[0053] The nucleophilic anion generator is not particularly limited as long as it generates a nucleophilic anion by heating and can sufficiently release carbon dioxide gas from the ethylene carbonate structure contained in the pressure-sensitive adhesive composition according to the present embodiment by the nucleophilic anion. Examples of the nucleophilic anion include fluoride ion (F - ), chloride ion (Cl - ), bromide ion (Br - ), iodide ion (I - ), hydroxide ion (OH - ) and the like, and among these, fluoride ions (F - ) and bromide ion (Br - ) is preferred, and fluoride ion (F - Examples of the cation constituting the nucleophilic anion generator include a quaternary ammonium cation, an imidazolium cation, a pyrrolidinium cation, a pyridinium cation, a piperidinium cation, a phosphonium cation, an alkali metal ion, an alkaline earth metal ion, and the like, and among these, a quaternary ammonium cation is preferred.
[0054] Specific preferred examples of the nucleophilic anion generator include tetrabutylammonium fluoride (TBAF), tetrabutylammonium bromide (TBAB), 1-ethyl-3-methylimidazolium bromide, tetrabutylphosphonium bromide, sodium hydroxide, etc., and among these, tetrabutylammonium fluoride (TBAF) and tetrabutylammonium bromide (TBAB) are preferred. These nucleophilic anion generators may be used alone or in combination of two or more.
[0055] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention. EXAMPLES
[0056] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.
[0057] Example 1-1 A solution containing 20 parts by mass of an ethylene carbonate-containing methacrylic monomer (monomer produced using carbon dioxide as a raw material; 2-oxo-1,3-dioxolan-4-yl)methyl methacrylate) in which n is 1 in the above-mentioned formula (3), 0.2 parts by mass of acrylic acid, 1 part by mass of polyoxyethylene polycyclic phenyl ether sulfate salt (manufactured by Nippon Nyukazai Co., Ltd., product name "Newcol 707SF") as an emulsifier, and 130 parts by mass of purified water was stirred at 70°C and 170 rpm.
[0058] Next, 0.3 parts by mass of ammonium persulfate (APS) was added to the above solution as a polymerization initiator, and the mixture was polymerized for 10 minutes by emulsion polymerization while stirring at 70° C. and 160 rpm to prepare a (meth)acrylic acid ester polymer. This resulted in an emulsion in which the (meth)acrylic acid ester polymer was dispersed as a dispersoid in water as a dispersion medium.
[0059] In the obtained emulsion, the mass ratio of the ethylene carbonate-containing acrylic monomer constituting the (meth)acrylic acid ester polymer (A) to acrylic acid was about 99: 1, and the molar ratio was about 37: 1. The solid content concentration of the above emulsion was calculated to be 14.4 mass%.
[0060] [Examples 1-2 to 1-5] Emulsions were prepared in the same manner as in Example 1, except that the composition of the (meth)acrylic acid ester polymer, the content of the ethylene carbonate-containing acrylic monomer in the (meth)acrylic acid ester polymer, the content of the emulsifier, and the content of purified water were changed as shown in Table 1. The solid content concentrations of the obtained emulsions were calculated and were as shown in Table 1.
[0061] [Examples 1 to 6] A solution containing 5 parts by mass of 4-(oxiran-2-ylmethoxy)butyl acrylate, 0.32 parts by mass of lithium bromide, and 24 parts by mass of N-N'-dimethylformamide was replaced with carbon dioxide gas in the system and then stirred at 60°C for 17 hours. After distilling off the N-N'-dimethylformamide under reduced pressure, ethyl acetate and purified water were added, followed by extraction and washing, and magnesium sulfate was added to the resulting organic layer for drying. After filtration, the ethyl acetate was distilled off under reduced pressure to obtain a pale yellow liquid (yield 96%).
[0062] The components in the resulting pale yellow liquid were subjected to 1H NMR and 13C NMR measurements, and were confirmed to be the ethylene carbonate-containing acrylic monomer (4-((2-oxo-1,3-dioxolan-4-yl)methoxy)butyl acrylate) in which n is 1 and m is 4 in the above-mentioned formula (4).
[0063] A solution containing 15 parts by mass of ethylene carbonate-containing methacrylic monomer (monomer produced using carbon dioxide as a raw material) in which n is 1 in the above-mentioned formula (3), 5 parts by mass of ethylene carbonate-containing acrylic monomer (monomer produced using carbon dioxide as a raw material) in which n is 1 and m is 4 in the above-mentioned formula (4) prepared as described above, 0.8 parts by mass of acrylic acid, 1 part by mass of polyoxyethylene polycyclic phenyl ether sulfate salt (manufactured by Nippon Nyukazai Co., Ltd., product name "Newcol 707SF") as an emulsifier, and 130 parts by mass of purified water was stirred under conditions of 70°C and 170 rpm.
[0064] Next, 0.3 parts by mass of ammonium persulfate (APS) was added to the above solution as a polymerization initiator, and the mixture was polymerized for 10 minutes by emulsion polymerization while stirring at 70° C. and 160 rpm to prepare a (meth)acrylic acid ester polymer. This resulted in an emulsion in which the (meth)acrylic acid ester polymer was dispersed as a dispersoid in water as a dispersion medium.
[0065] In the obtained emulsion, the mass ratio of the ethylene carbonate-containing acrylic monomer constituting the (meth)acrylic acid ester polymer (A) to acrylic acid was about 96: 4, and the molar ratio was about 8.7: 1. The solid content concentration of the above emulsion was calculated to be 15.8 mass%.
[0066] [Examples 1 to 7] A solution containing 5 parts by mass of ethylene carbonate-containing methacrylic monomer (monomer produced using carbon dioxide as a raw material) in which n is 1 in the above-mentioned formula (3), 45 parts by mass of n-butyl acrylate, 50 parts by mass of 2-ethylhexyl acrylate, 0.5 parts by mass of acrylic acid, 1 part by mass of polyoxyethylene polycyclic phenyl ether sulfate salt (manufactured by Nippon Nyukazai Co., Ltd., product name "Newcol 707SF") as an emulsifier, and 150 parts by mass of purified water was stirred under conditions of 70°C and 130 rpm.
[0067] Next, 0.3 parts by mass of ammonium persulfate (APS) was added to the above solution as a polymerization initiator, and the mixture was polymerized for 120 minutes by emulsion polymerization while stirring at 70°C and 130 rpm to prepare a (meth)acrylic acid ester polymer. This resulted in an emulsion in which the (meth)acrylic acid ester polymer as dispersoid was dispersed in water as a dispersion medium. The solid content concentration of each of the obtained emulsions was calculated and was as shown in Table 1.
[0068] [Examples 1-8] Emulsions were prepared in the same manner as in Example 1-76, except that the monomer composition of the (meth)acrylic acid ester polymer was changed as shown in Table 1. The solid content concentration of each of the obtained emulsions was calculated and was as shown in Table 1.
[0069] Details of the abbreviations and the like used in Table 1 (and Table 2 described below) are as follows: ECMA: (2-oxo-1,3-dioxolan-4-yl)methyl methacrylate ECMBA: 4-((2-oxo-1,3-dioxolan-4-yl)methoxy)butyl acrylate AAc: acrylic acid BA: n-butyl acrylate 2EHA: 2-ethylhexyl acrylate
[0070] [Test Example 1-1] (Measurement of particle size (D50)) For the emulsions obtained in the examples, the particle size distribution of the dispersed substance ((meth)acrylic acid ester polymer) in the emulsion was measured by dynamic light scattering using a dynamic light scattering particle size distribution measuring device (manufactured by Microtrack-Bell, product name "Nanotrac Wave") to determine the particle size (D50). The results are shown in Table 1.
[0071] [Test Example 1-2] (Evaluation of stability) The emulsions obtained in the examples were stored at room temperature for 6 months and then their average particle size (D50) was measured. The changes from the average particle size (D50) immediately after production were confirmed and the stability was evaluated based on the following criteria. The results are shown in Table 1. 〇: No change ×: Changed
[0072] [Test Example 1-3] (Observation of structural color) The emulsion obtained in the example was dropped onto a glass substrate and dried at room temperature (20°C) and 50% RH. The obtained film was visually observed by multiple evaluators and evaluated for the color tone of the structural color. The evaluation results are shown in Table 1.
[0073] [Test Example 1-4] (Calculation of CO2 fixation amount) The amount (mass ratio) of carbon dioxide used (fixed) in the emulsion was calculated as the amount of CO2 fixed from the blending amount of ethylene carbonate-containing acrylic monomer in the emulsion obtained in Examples 1-1 to 1-7. Specifically, the molecular weight of CO2 (=44) was divided by the molecular weight of ethylene carbonate-containing acrylic monomer (A) (=158) or the molecular weight of ethylene carbonate-containing acrylic monomer (B) (=244) and expressed as a percentage. The results are shown in Table 1.
[0074] [Table 1]
[0075] As shown in Table 1, it was confirmed that stable emulsion particles were obtained in Examples 1-1 to 1-7. It was also confirmed that the emulsions of Examples 1-1, 1-2, 1-4, and 1-5 had structural coloring, and it was understood that the hue of the observed structural color changed when the particle size changed.
[0076] Example 2-1 95 parts by mass of n-butyl acrylate and 5 parts by mass of acrylic acid were copolymerized by emulsion polymerization to obtain a (meth)acrylic acid ester copolymer as an adhesive component. 100 parts by mass of the (meth)acrylic acid ester copolymer (solid content equivalent value 36% by mass, same below) was mixed with 10 parts by mass of the emulsion produced in Example 1-1 to obtain a coating solution of an adhesive composition with a solid content concentration of 33% by mass.
[0077] The obtained coating solution was applied to the release-treated surface of the release sheet by a coater. The coating layer was then heated at 100°C for 2 minutes to form a resin film. Next, the resin film on the release sheet obtained above was attached to the release-treated surface of another release sheet so as to be in contact with the resin film, to produce an adhesive sheet having a resin film (adhesive layer) of 25 μm in thickness, i.e., an adhesive sheet having a structure of release sheet / adhesive layer (thickness: 25 μm) / release sheet.
[0078] [Examples 2-2 to 2-4 and Comparative Examples 2-1 to 2-3] Except for changing the composition and content of the (meth)acrylic acid ester copolymer as the adhesive component, and the type and content of the emulsion used as shown in Table 2, an adhesive sheet was prepared in the same manner as in Example 2-1.
[0079] [Test Example 2-1] (Measurement of gel fraction) The adhesive sheets produced in Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-3 were cut to a size of 80 mm x 80 mm, the adhesive layer was wrapped in a polyester mesh (mesh size 200), and the mass was measured using a precision balance. The mass of the mesh alone was subtracted to calculate the mass of the adhesive alone. This mass was designated M1.
[0080] Next, the adhesive wrapped in the polyester mesh was immersed in ethyl acetate at room temperature (23°C) for 72 hours. The adhesive was then removed and air-dried for 24 hours in an environment with a temperature of 23°C and a relative humidity of 50%, and then dried in an oven at 80°C for 12 hours. After drying, the mass was weighed using a precision balance, and the mass of the adhesive alone was calculated by subtracting the mass of the mesh alone. The mass at this time was designated M2. The gel fraction (%) was expressed as (M2 / M1) x 100. The gel fraction of the adhesive was calculated from this. The results are shown in Table 2.
[0081] [Test Example 2-2] (Haze value measurement) The adhesive layer of the adhesive sheet produced in Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-3 was attached to glass to prepare a measurement sample. After background measurement was performed in an empty state, the haze value of the measurement sample was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "SH-7000") in accordance with JIS K7136:2000. The results are shown in Table 2.
[0082] [Test Example 2-3] (Measurement of total light transmittance) The adhesive layer of the adhesive sheet produced in Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-3 was attached to glass to prepare a measurement sample. After background measurement was performed in an empty state, the total light transmittance of the measurement sample was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "SH-7000") in accordance with JIS K7361-1:1997. The results are shown in the table.
[0083] [Test Example 2-4] (Measurement of chromaticity b*) The chromaticity b* defined by the CIE1976L*a*b* color system was measured for the adhesive layer side of the adhesive sheets produced in Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-3 using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "SH-7000"). The results are shown in Table 2.
[0084] [Test Example 2-5] (Measurement of adhesive strength) One of the release sheets of the adhesive sheets produced in Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-3 was peeled off, and the exposed adhesive layer was attached to an easy-adhesion layer of a polyethylene terephthalate (PET) film (manufactured by Toyobo Co., Ltd., product name "Cosmoshine A4360", thickness: 50 μm) having an easy-adhesion layer to obtain a release sheet / adhesive layer / PET film laminate. The obtained laminate was cut into a width of 25 mm and a length of 100 mm.
[0085] Next, in an environment of 23°C and 50% RH, the release sheet was peeled off from the laminate, and the exposed adhesive layer was attached to a soda lime glass plate (manufactured by Nippon Sheet Glass Co., Ltd., product name "Soda Lime Glass", thickness: 1.1 mm), and then left for 24 hours under conditions of 23°C and 50% RH. Then, the adhesive strength was measured when the laminate of the PET film and the adhesive layer was peeled off from the adherend using a tensile tester (manufactured by Orientec Co., Ltd., Tensilon) at a peel speed of 300 mm / min and a peel angle of 180 degrees. The measurement was performed according to JIS Z0237:2009 under conditions other than those described here. The results are shown in Table 2.
[0086] [Test Example 2-6] (Measurement of storage modulus) The adhesive layers of the adhesive sheets produced in Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-3 were laminated in multiple layers to a thickness of 0.8 mm to form a laminate. A cylindrical body with a diameter of 8 mm (height of 0.8 mm) was punched out from the resulting laminate of adhesive layers to form a sample. The storage modulus G' and loss tangent (tan δ) of the above sample were measured at -20°C, 25°C, and 100°C by a torsional shear method using a viscoelasticity measuring device (manufactured by Anton Paar, product name "MCR302") in accordance with JIS K7244-6 under the following conditions. The results are shown in Table 2. Measurement frequency: 1Hz Measurement temperature: -20℃, 25℃, 100℃
[0087] [Test Example 2-7] (Calculation of CO2 fixation amount) The amount (mass ratio) of carbon dioxide used (fixed) in the adhesive sheet was calculated as the amount of CO2 fixed from the blending amount of ethylene carbonate-containing acrylic monomer in the adhesive sheet produced in the examples and comparative examples. Specifically, the molecular weight of CO2 (=44) was divided by the molecular weight of ethylene carbonate-containing acrylic monomer (A) (=158) and expressed as a percentage. The results are shown in Table 2.
[0088] [Table 2]
[0089] As shown in Table 2, the pressure-sensitive adhesive sheets produced in Examples 2-1 to 2-4 were able to fix a predetermined amount of carbon dioxide and had physical properties that made them suitable for a variety of applications.
[0090] [Preparation Example 1] 95 parts by mass of n-butyl acrylate and 5 parts by mass of acrylic acid were copolymerized by emulsion polymerization to obtain a (meth)acrylic acid ester copolymer as the main material of the adhesive component. 100 parts by mass of the main material (solid content equivalent value 36% by mass, same below) was mixed with 10 parts by mass of the emulsion produced in Example 1-1 and 2 parts by mass of tetrabutylammonium bromide (TBAB) as a catalyst to obtain a coating solution of an adhesive composition with a solid content concentration of 33% by mass.
[0091] The obtained coating solution was applied to the release-treated surface of a release sheet (a release sheet in which one side of a polyethylene terephthalate film was treated with a silicone-based release agent, manufactured by Lintec Corporation, product name "SP-PET752150") using a coater. Then, the coating layer was heated at 100°C for 2 minutes to form a resin film. Next, the release-treated surface of another release sheet (a release sheet in which one side of a polyethylene terephthalate film was treated with a silicone-based release agent, manufactured by Lintec Corporation, product name "SP-PET381031") was attached so as to contact with the resin film on the release sheet obtained above, to produce an adhesive sheet having a resin film (adhesive layer) with a thickness of 25 μm, that is, an adhesive sheet having a configuration of release sheet / adhesive layer (thickness: 25 μm) / release sheet.
[0092] [Preparation Example 2] An adhesive sheet was obtained in the same manner as in Preparation Example 1, except that the content of the emulsion was 20 parts by mass and the content of the catalyst (TBAB) was 4 parts by mass.
[0093] [Preparation Example 3] An adhesive sheet was obtained in the same manner as in Preparation Example 1, except that the content of the emulsion was 20 parts by mass and 4 parts by mass of tetrabutylammonium fluoride (TBAF) was used as the catalyst.
[0094] [Preparation Example 4] 100 parts by mass of the emulsion produced in Example 1-1 and 10 parts by mass of tetrabutylammonium fluoride (TBAF) as a catalyst were mixed to obtain a coating solution of a resin composition with a solid content concentration of 33% by mass. The obtained coating solution was applied to the release-treated surface of a release sheet (a release sheet in which one side of a polyethylene terephthalate film was treated with a silicone-based release agent, manufactured by Lintec Corporation, product name "SP-PET752150") using a coater. The coating layer was then heated at 100°C for 2 minutes to form a resin film (thickness: 25 μm).
[0095] [Preparation Example 5] A resin film was obtained in the same manner as in Preparation Example 4, except that 30 parts by mass of tetrabutylammonium bromide (TBAB) was used as the catalyst.
[0096] [Test Example 3-1] (Measurement of 5% weight loss temperature) The 5% weight loss temperature of the adhesive sheets or resin films produced in Production Examples 1 to 5 was measured using a simultaneous differential thermal / thermogravimetric analyzer (manufactured by Shimadzu Corporation, product name "DTG-60") in accordance with JIS K7120: 1987. The results are shown in Table 3.
[0097] [Test Example 3-2] (Evaluation of foaming properties) The coating solution of the resin composition of Preparation Examples 1 to 5 was applied by a coater to the aluminum foil surface of a composite substrate (PET50A4360 Alpet manufactured by Toyobo Co., Ltd., thickness: 40 μm) in which an aluminum foil and a polyethylene terephthalate film were bonded together, and the coating layer was heated at 100° C. for 2 minutes to form a resin film (thickness: 25 μm). Next, the exposed surface of the resin film was attached to a glass plate, which was used as a bubble confirmation sample. These bubble confirmation samples were heated by placing them in a thermostatic chamber at 180° C. for 1 minute, and the presence or absence of bubbles at the interface between the pressure-sensitive adhesive layer and the glass plate was confirmed before and after the heating. Then, the foaming property was evaluated based on the following criteria. The results are shown in Table 2. ⊚: Air bubbles were observed all over the interface. ◯: Air bubbles were partially observed at the interface. ×: Almost no air bubbles were observed at the interface.
[0098] [Table 3]
[0099] As shown in Table 3, the pressure-sensitive adhesive sheets or resin films according to Preparation Examples 1 to 5 were found to be excellent in the evaluation results of foaming properties (ie, they generated a large amount of bubbles).
[0100] The above results are presumably due to the fact that, in the presence of an anion having nucleophilicity, the ethylene carbonate structure in the (meth)acrylic acid ester polymer performs a nucleophilic attack on the carbon atom constituting the carbonyl group in the ethylene carbonate structure in the pressure-sensitive adhesive layer or resin film according to Preparation Examples 1 to 5, and the anion efficiently decomposes the ethylene carbonate structure by heat. That is, in Preparation Examples 1 to 5, it is presumed that carbon dioxide is released from the pressure-sensitive adhesive layer due to the decomposition of the ethylene carbonate structure, which accelerates the weight loss and generates a large number of bubbles. [Industrial Applicability]
[0101] The emulsion of the present invention can fix carbon dioxide and is useful for environmental protection. The emulsion of the present invention is also useful in a wide range of fields, such as paints, adhesives, pressure sensitive adhesives, paper processing, dyes, fiber processing, printing inks, cement admixtures, coating agents, and films. The emulsion of the present invention has structural coloring properties, and is therefore suitable as a material for structural color-exhibiting objects. The emulsion of the present invention is also suitable for use in the manufacture of products that require easy dismantling, since it is decomposed by heat treatment together with a catalyst and releases carbon dioxide.
Claims
1. As a monomer unit constituting the polymer, 【Chemistry 1】 2. An emulsion comprising, as a dispersoid, a (meth)acrylic acid ester polymer containing an ethylene carbonate-containing acrylic monomer having an ethylene carbonate structure represented by the formula:
2. 2. The emulsion according to claim 1, wherein the (meth)acrylic acid ester polymer contains the ethylene carbonate-containing monomer in an amount of 1% by mass or more and 99.9% by mass or less as a monomer unit constituting the polymer.
3. 2. The emulsion according to claim 1, wherein the ethylene carbonate-containing acrylic monomer is a compound represented by any one of the following formulas (2) to (4): 【Chemistry 2】 (In the formula, n represents an integer of 0 or more.) 【Chemistry 3】 (In the formula, n represents an integer of 0 or more.) 【Chemistry 4】 (In the formula, n and m represent integers of 0 or more. X represents hydrogen or a methyl group.)
4. 2. The emulsion according to claim 1, wherein the particle diameter (D50) of the dispersoid is 10 nm or more and 1 μm or less.
5. 2. The emulsion according to claim 1, wherein the (meth)acrylic acid ester polymer contains acrylic acid as a monomer unit constituting the polymer.
6. 2. The emulsion according to claim 1, wherein the (meth)acrylic acid ester polymer is obtained by emulsion polymerization of monomer units containing the ethylene carbonate-containing acrylic monomer.
7. 2. The emulsion according to claim 1, which contains water as a dispersion medium.
8. An article comprising a resin film formed from a resin composition containing the emulsion according to any one of claims 1 to 7.
9. The resin film is a pressure-sensitive adhesive layer, The article is a pressure-sensitive adhesive sheet.
9. The article of claim 8.
Citation Information
Patent Citations
Adhesive composition, adhesive, laminate, and application of the same
JP2023035332A
JP214208A